Out of Anatolia: longitudinal gradients in genetic diversity support an eastern origin for a circum‐Mediterranean oak gallwasp Andricus quercustozae - Antonis Rokas; Rachel J. Atkinson; Lucy Webster; György Csóka; Graham N. Stone (Molecular Ecology, 2003)
Many studies have addressed the latitudinal gradients in intraspecific genetic diversity of European taxa generated during postglacial range expansion from southern refugia. Although Asia Minor is known to be a centre of diversity for many taxa, relatively few studies have considered its potential role as a Pleistocene refugium or a potential source for more ancient westward range expansion into Europe. Here we address these issues for an oak gallwasp, Andricus quercustozae (Hymenoptera: Cynipidae), whose distribution extends from Morocco along the northern coast of the Mediterranean through Turkey to Iran. We use sequence data for a fragment of the mitochondrial gene cytochrome b and allele frequency data for 12 polymorphic allozyme loci to answer the following questions: (1) which regions represent current centres of genetic diversity for A. quercustozae ? Do eastern populations represent one refuge or several discrete glacial refugia? (2) Can we infer the timescale and sequence of the colonization processes linking current centres of diversity? Our results suggest that A. quercustozae was present in five distinct refugia (Iberia, Italy, the Balkans, southwestern Turkey and northeastern Turkey) with recent genetic exchange between Italy and Hungary. Genetic diversity is greatest in the Turkish refugia, suggesting that European populations are either (a) derived from Asia Minor, or (b) subject to more frequent population bottlenecks. Although Iberian populations show the lowest diversity for putatively selectively neutral markers, they have colonized a new oak host and represent a genetically and biologically discrete entity within the species.